Examining the Role of Information Technology, Creativity, and Business Capital in Supporting MSMEs Sustainability in Bandar Lampung's Fashion Industry - Nesya Maharani Putri; Rr Erlina; Nurul Husna (Global Management: International Journal of Management Science and Entrepreneurship, 2024)
The Indonesian economy is largely driven by Micro, Small, and Medium Enterprises (MSMEs), which play a vital role in economic growth. MSMEs have proven resilient during economic crises. This study analyzes the impact of Information Technology, Creativity, and Business Capital on MSME sustainability using quantitative methods. Data from 115 MSMEs were gathered through structured questionnaires. The t-test results reveal that Creativity significantly influences MSME sustainability. Similarly, Information Technology and Business Capital have significant positive impacts, aligning with existing literature. The coefficient of determination (R²) of 43.7% shows that these three variables explain variations in MSME sustainability. To enhance Information Technology utilization, MSMEs should improve data systems and provide training for managers. Creativity can be strengthened by fostering innovation and organizing brainstorming sessions. For Business Capital, MSMEs need investment strategies focused on long-term growth. Additionally, increasing market value through product innovation and collaboration is crucial. These efforts are expected to support the sustainability of MSMEs in Bandar Lampung’s fashion sector.